Facts, values, and Attention-Deficit Hyperactivity Disorder (ADHD): an update on the controversies - Johnston Josephine; Parens Erik (BMC, 2009)
Abstract The Hastings Center, a bioethics research institute, is holding a series of 5 workshops to examine the controversies surrounding the use of medication to treat emotional and behavioral disturbances in children. These workshops bring together clinicians, researchers, scholars, and advocates with diverse perspectives and from diverse fields. Our first commentary in CAPMH, which grew out of our first workshop, explained our method and explored the controversies in general. This commentary, which grows out of our second workshop, explains why informed people can disagree about ADHD diagnosis and treatment. Based on what workshop participants said and our understanding of the literature, we make 8 points. (1) The ADHD label is based on the interpretation of a heterogeneous set of symptoms that cause impairment. (2) Because symptoms and impairments are dimensional, there is an inevitable "zone of ambiguity," which reasonable people will interpret differently. (3) Many other variables, from different systems and tools of diagnosis to different parenting styles and expectations, also help explain why behaviors associated with ADHD can be interpreted differently. (4) Because people hold competing views about the proper goals of psychiatry and parenting, some people will be more, and others less, concerned about treating children in the zone of ambiguity. (5) To recognize that nature has written no bright line between impaired and unimpaired children, and that it is the responsibility of humans to choose who should receive a diagnosis, does not diminish the significance of ADHD. (6) Once ADHD is diagnosed, the facts surrounding the most effective treatment are complicated and incomplete; contrary to some popular wisdom, behavioral treatments, alone or in combination with low doses of medication, can be effective in the long-term reduction of core ADHD symptoms and at improving many aspects of overall functioning. (7) Especially when a child occupies the zone of ambiguity, different people will emphasize different values embedded in the pharmacological and behavioral approaches. (8) Truly informed decision-making requires that parents (and to the extent they are able, children) have some sense of the complicated and incomplete facts regarding the diagnosis and treatment of ADHD.